P170 Injury effects on short-and long-term lost-work outcomes among youth and other agricultural operation household members in the midwest united states. (1st September 2016) - Gerberich, Susan; Ryan, Andrew; Alexander, Bruce; Renier, Colleen
Abstract : Background: More than half of youth living on agricultural operations perform work or chores on these operations and experience injury rates per work hour similar to adults. Objectives: Analyse associations between injuries incurred by youth (<20 years) and short- and long-term changes in work-time lost among injured youth and other agricultural household members. Methods: A random sample of 6, 400 operations was selected from each state (Minnesota, Wisconsin, North Dakota, South Dakota, and Nebraska), using the US Department of Agriculture, National Agricultural Statistics Service's Master ListFrame. Using computer-assisted telephone interviews, operations were screened for eligibility: agricultural households with youth actively farming/ranching as of January 1, 2007. Baseline data were collected from 1, 459 eligible agricultural operations. Two six-month injury data collection periods followed baseline collection; annual follow-up evaluation data were collected for two years. Case households included youth with agricultural or non-agricultural injuries; control households with no injured youth, were randomly selected (3:1 ratio). Changes between baseline and follow-up were analysed, comparing case and control households. Controlling for baseline lost-work time, multivariable logistic regression models characterised associations between case-control household status and long-term lost-work outcomes. Results/outcome: The rate (95% C.I.) of agricultural versus non-agricultural injury events per 1, 000 persons was four times higher among youth (94.4; 80.3–111.1 and 23.1; 17.0–31.3); 21% of agricultural, versus 9% of non-agricultural youth injuries, resulted in lost work time of ≥7 days. One-year following the injury reporting period, case compared with control households with children reporting severe injuries (restricted activities ≥7 days), increased the risk for adult members to miss operation-related days of work or chores because of the youths' health conditions (OR 2.4; C.I., 1.0–5.4). Significance: This study is among the few to address serious deficiencies in knowledge about long-term consequences and overall burden associated with injuries incurred by youth living on agricultural operations.